Understanding price volatility and seasonality in agricultural commodities in India - Md Yeasin; Purushottam Sharma; Ranjit Kumar Paul; Dinesh Chand Meena; Md Ejaz Anwer (Agricultural Economics Research Review, 2024)
The volatility in prices of agricultural commodities is a major concern for policymakers, researchers, and value chain participants, including farmers. The study examines the trend and pattern of agricultural price volatility and its seasonality using monthly data from January 2010 to December 2022. The fixed effects model has been used to decipher the effect of market arrivals, rainfall and pandemic shock on the prices. The results have revealed that prices of vegetables were most volatile, followed by oilseeds and pulses. The seasonality pattern of volatility has shown general peaks during the pre-harvest and harvest periods and troughs during the post-harvest period. The rainfall affected the prices of mainly rainfed crops and the effect of the pandemic has been found to be positive for many of the agri-commodities. Strengthening post-harvest value chain institutions and related infrastructure, and increasing of competition in the markets would help integrate markets and reduce price volatility.